Influence of acute glycaemic level on measures of myocardial infarction in non-diabetic pigs. (2nd November 2015) - Diemar, Sarah S.; Sejling, Anne-Sophie; Iversen, Kasper K.; Engstrøm, Thomas; Honge, Jesper L.; Tønder, Niels; Vejlstrup, Niels; Idorn, Manja; Ekström, Kathrine; Pedersen-Bjergaard, Ulrik; Thorsteinsson, Birger; Dalsgaard, Morten
Abstract>: Objective. Patients with diabetes are at increased risk of experiencing myocardial infarction. The influence of the prevailing plasma glucose level on infarction and mortality after acute ischaemia is however unknown. The aim was to study the effect of the acute plasma glucose level on the myocardial infarction size in a closed-chest pig model. Design. 38 non-diabetic pigs were randomised to hypoglycaemic (1.8–2.2 mmol/l; n = 15), normoglycaemic (5–7 mmol/l; n = 12) or hyperglycaemic glucose clamping (22–23 mmol/l; n = 11). After 30 min within glucose target myocardial infarction was induced for 30 min followed by reperfusion for 120 min. Hereafter the heart was double-stained to delineate infarction from viable tissue within the area at risk. Results. Mean infarction size was 201 ± 35 mm 2 (mean ± SEM) in the hypoglycaemic group, 154 ± 40 mm 2 in the normoglycaemic group and 134 ± 40 mm 2 in the hyperglycaemic group, with no differences in infarction size, infarct/area at risk ratio or troponin T levels between the groups. There was no difference in incidence of ventricular fibrillation or mortality between the groups. Conclusion. No statistically significant associations were observed between the acute glycaemic level and measures of myocardial infarction, rates of ventricular fibrillation and subsequent premature death in the setting of acute ischaemia and reperfusion.